Exploring AI Integration in Financial Institutions: Challenges, Compliance, and Quality Assurance's Role in Security - Tasneem Rahmatullah; Nurul Nadia Nozlan; Tasneem Rahmatullah; Nurul Nadia Nozlan (Journal of Central Banking Law and Institutions, 2026)
The use of Artificial Intelligence (AI) in financial institutions offers significant opportunities while raising concerns about regulatory compliance, security, and the changing function of Quality Assurance (QA). This research explores the impact of AI integration on fairness, transparency, and financial inclusion in the Malaysian financial sector, and investigates the challenges QA professionals face in navigating the dynamic regulatory landscape, with a focus on data privacy and cross-border regulations. It also examines QA’s role in mitigating technological risks, addressing security vulnerabilities, and supporting organisational transformation. Employing a qualitative methodology, the study combines a desk review of existing literature and a semi-structured interview with an Enterprise Architecture and Quality Assurance Specialist from Bank Muamalat Malaysia Berhad (BMMB). By triangulating theoretical frameworks with practical insights from industry professionals, the study finds that QA plays a pivotal role in ensuring the responsible and secure implementation of AI. Specifically, findings highlight the need for robust QA processes to address algorithmic bias, ensure transparency in AI decision-making, and promote inclusive access to financial services. This research contributes to the discourse on responsible AI adoption in the financial sector by providing practical recommendations for financial institutions seeking to implement responsible AI strategies. This research was conducted in accordance with ethical research standards.